The video assistant referee in football - Teixeira da Silva, J. A.; Nazarovets, S.; Carboch, J.; Deutscher, C.; Almeida, C. H.; Webb, T.; Scelles, N. (Sports Engineering, 2024)
The video assistant referee (VAR), popularized in football (soccer), has been decisive in many games played in several international and domestic competitions ever since the Fédération Internationale de Football Association (FIFA) formalized its use for the first time in the 2018 Men`s Football World Cup. Serving as a support tool for on-field referees, it is not only a game unifier but also a conflict pacifier by using a technology-based method to objectively appreciate whether human decisions were accurate and fair or erroneous and thus in need of correction. Given the overwhelming support evidenced by its broad adoption, but also some criticisms and concerns about this technology, an objective assessment of the growing literature on VAR is timely to take stock of what is known and what is still unknown about its use and perception. Using primarily indexed English literature from 2018 to 2024, this narrative review aims to gauge four main talking points related to VAR, including, but not limited to, the technology used, why VAR is perceived as controversial, and its perception in a socio-cultural context. This review underscores the positive perception of referees towards VAR, highlighting improved decision accuracy and minimal match disruption. Fans and media express trust in VAR, but call for refinements. Concerns about in-stadium communication with spectators suggest a need for enhanced decision transparency. We also acknowledge limitations, including language bias, literature (un)availability and sex-based disparities, while proposing future research avenues. Overall, VAR has become integral to football, shaping its officiating landscape, and inviting continuous improvement.